Učinkovitost Uredbe o postopkih v sporih majhne vrednosti in analiza predvidenih novosti po predlogu o spremembi uredbe - Tjaša Ivanc (LeXonomica, 2021)
The effectiveness of the regulation establishing a European small claims procedure and the analysis of foreseen novelties under the proposal for amendments of the regulation. This paper deals with a European small claims procedure, which was the first to introduce the adversarial principle with the objective to simplify and speed up the settlement of disputes with cross-border elements and to reduce costs. European small claims procedure is an alternative proceeding, which allows customers to opt for either procedure under the national laws of the Member States or supranational procedures. This is a European instrument that allows mutual recognition of judgments in civil matters and enforcement of judgments in the Member States with the exclusion of the exequatur. Regulation no. 861/2007 on the procedure for Small Claims provides written procedure on the basis of standard forms promotes the use of modern communication technologies and lays down minimum standards for the protection of procedural rights. Despite the advantages, there are courts in the Member States which are hardly aware of this procedure. The author presents normative and empirical aspects of the Regulation no. 861/2007 and highlights current weaknesses, which are the reason that the use of this transnational procedure in practice did not come to life as expected after the regulation was adopted.Povzetek. Ta prispevek obravnava evropski postopek v sporu majhne vrednosti, ki je prvi uvedel kontradiktorni postopek, s ciljem poenostavitve in pospešitve reševanja sporov s čezmejnim elementom in znižanjem stroškov. Evropski postopek majhne vrednosti je alternativni postopek, kar omogoča strankam, da se odločijo bodisi za postopek na podlagi zakonov držav članic ali za nadnacionalni postopek. Gre za evropski instrument, ki omogoča medsebojno priznanje sodnih odločb v civilnih zadevah in izvršitev sodnih odločb v državah članicah z izključitvijo eksekvature. Uredba št. 861/2007 o postopkih v sporih majhne vrednosti predvideva pisen postopek na podlagi standardnih obrazcev, pospešuje uporabo modernih komunikacijskih tehnologij in določa minimalne procesne standarde za varstvo pravic. Kljub prednostim pa so sodišča s tem postopkom v državah članicah slabo seznanjena. Avtorica predstavi normativni in empirični vidik Uredbe št. 861/2007 ter izpostavi trenutne slabosti, zaradi katerih uporaba tega nadnacionalnega postopka v praksi ni zaživela, kot je bilo pričakovano ob njenem sprejetju.